Analisis Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Rasio Profitabilitas (ROA) Return On Asset - Juan Marshaputra; Wirman Wirman (Peneliti.net, 2023)
The research writing has the aim of seeing and analyzing how an influence of mudharabah financing and musyarakah financing at PT Bank Syariah Indonesia Tbk on profitability with the variable studied is Return On Asset (ROA). This study uses financial statement data every month taken in the 2018-2021 timeframe published at www.ojk.go.id. This research for independent variables (X) includes: Mudharabah Financing and Musyarakah Financing. The use of the dependent variable (Y) of this study is Return On Asset (ROA) which is processed by descriptive statistical methods, multiple linear regression analysis, simultaneous test (F test) and partial test (t test) and the data is processed using SPSS 22 software. The results of the t test found that mudharabah financing has no effect on the Return On Asset ratio but the X2 variable, namely musyarakah financing, has the result of affecting the bank's Return On Asset. Test simultaneously or together the 2 variable financing affects the Return On Asset of PT Bank Syariah Indonesia.